Antara Anak Dan Teknologi: Butuh Atau Bunuh? - sari fidiyah sari (Publikasi Indonesia, 2022)
The existence of technology development is a manifestation of modern life that everyone of early childhood to adults is able to access the technology. The increasingly heavy technological development makes the pattern of education from parents for children to experience changes to the number of parents who begin to mix technology in children’s excitement in providing knowledge stimulation to support their education but how does the technology impact for childern, does ut need or kill?. Technology is not a thing that can kill amak in the aspect of its development if his parents can be where they exchange information they get from technology, can be a safety for their children, and performs all informations of children get based on the description, this study aims to optimze the role of children and technology using a qualitative approach with the study method.